The molecular virology of coronaviruses - Hartenian, Ella; Nandakumar, Divya; Lari, Azra; Ly, Michael; Tucker, Jessica M.; Glaunsinger, Britt A. (The Journal of biological chemistry, 2020)
Few human pathogens have been the focus of as much concentrated worldwide attention as severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), the cause of COVID-19. Its emergence into the human population and ensuing pandemic came on the heels of severe acute respiratory syndrome coronavirus (SARS-CoV) and Middle East respiratory syndrome coronavirus (MERS-CoV), two other highly pathogenic coronavirus spillovers, which collectively have reshaped our view of a virus family previously associated primarily with the common cold. It has placed intense pressure on the collective scientific community to develop therapeutics and vaccines, whose engineering relies on a detailed understanding of coronavirus biology. Here, we present the molecular virology of coronavirus infection, including its entry into cells, its remarkably sophisticated gene expression and replication mechanisms, its extensive remodeling of the intracellular environment, and its multifaceted immune evasion strategies. We highlight aspects of the viral life cycle that may be amenable to antiviral targeting as well as key features of its biology that await discovery.